KYAI SEBAGAI LEADER DALAM MEMBENTUK KECERDASAN SPIRITUAL SANTRI DI PONDOK PESANTREN RAUDLATUL HIKMAH AS SYAFII - Masruroh, Diana; Khumaidi, Ahmad; Fatimah, Nur (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
The purpose of this research is to find out the kyai leadership model and the strategies used by kyai in developing the spiritual intelligence of students of the Raudlatul Hikmah As Syafii Islamic Boarding School. The research methodology used is qualitative descriptive. Data collection was carried out through interviews, observations, and in-depth documentation. The results of the study show that the kyai leadership model in shaping the spiritual intelligence of students includes charismatic and democratic leadership. The strategies applied by the kyai to form the spiritual intelligence of students include the provision of moral education, spiritual assignments, and religious forums. These findings show that the strategy has succeeded in improving the quality of students' spiritual intelligence. The model and strategy applied by kyai in shaping the spiritual intelligence of students at the Raudlatul Hikmah As Syafii Islamic Boarding School proved to be very effective.